Horizontal, vertical and conglomerate investments in the Italian logistics industry: drivers and strategies - Elena Maggi; Ilaria Mariotti; Elia Stefano (European Regional Science Association (ERSA), 2010)
The internationalisation of the logistics and transport industry has massively increased in the last three decades. Given this rapid growth, fully understanding the determinants and implications of this phenomenon has been high on the agenda for both policy makers as well as academics. The inward FDI (greenfield and M&A), on which the present paper focuses, can be driven by three different strategies: horizontal, vertical and conglomerate integrations. In case of horizontal integration, the investment is carried out in the same industry of the parent multinational enterprise (MNE) (i.e., a MNE operating in the maritime transport undertakes an investment in maritime transport). When vertical integration takes place, the MNE invests in different stages of the same industry (i.e., an investment of a maritime MNE in a terminal operator.) Finally, a conglomerate integration occurs when the investment in a logistics activity is carried out by a non-logistics MNE (i.e., a manufacturing MNE). The three strategies are moved by different drivers, going from "increasing market power" to "reducing transaction costs". As concerns Italy, that is the country of interest of the present paper, in the last decade the logistics and transport industry has been increasingly interested by inward FDI, which are concentrated in the supply of integrated and intermodal services or other higher value added services than the pure goods and passengers transport. The integration strategies are a relatively unexplored area in logistics research. The present paper extends the existing literature on the integration strategies undertaken by foreign MNE investing in the Italian market, by exploring the drivers behind them. Descriptive statistics and econometric analyses are carried out. The data used come from the LogINT database, developed by the Laboratory of Economics, Logistics and Territory of DiAP-Politecnico di Milano, and covers the period 2000 - 2009. Additional qualitative data about the motivations behind the integrations strategies, undertaken by the foreign logistics MNE, have been collected in the logistics magazines and the companies' web sites.
Keywords: 330